Genomic Characteristics and Selection Signatures in Indigenous Chongming White Goat (Capra hircus) - Gao, Jun; Lyu, Yuhua; Zhang, Defu; Reddi, Kiran Kumar; Sun, Fengping; Yi, Jianzhong; Liu, Chengqian; Li, Hong; Yao, Huijuan; Dai, Jianjun; Xu, Fuyi (Frontiers in Genetics, 2020)
The Chongming (CM) white goat is an indigenous goat breed, which demonstrates unique traits secondary to adaptation to the local environment and artificial selection. By performing whole genome re-sequencing, we generated coverage (14-20×) sequences from 10 domestic goat breeds to explore their genomic characteristics and selection signatures in the CM breed. We identified a total of 23,508,551 SNPs and 2,830,800 indels after performing read mapping and variant calling. We specifically identified 271,713 SNPs and 24,843 indels unique to the CM breed in comparison with the other nine goat breeds. Missense (SIFT<0.05), frameshift, splice-site, start-loss, stop-loss, and stop-gain variants were identified in 183 protein-coding genes. Of the 183, 36 genes, including AP4E1, FSHR, COL11A2, and DYSF, are involved in phenotype ontology terms related to the nervous system, short stature, and skeletal muscle morphology. Moreover, based on genome-wide FST calculation, we further identified hundreds of selection signature genes between CM and the other 9 goat breeds. These genes are significantly associated with nervous system traits (ZMYND11, RAF1, and CUX1), growth (UCP2, UCP3, PAH, TSHR, FGFR1, ERLIN2, and ZNF703) and coat color (RALY, ASIP, AHCY, and KITLG). Our results suggest that the CM breed may be differentiated from other goat breeds in terms of nervous system structure due to natural or artificial selection. The whole genome analysis for CM breed from our study provides an improved understanding of genetic diversity and trait exploration for this indigenous goat breed.